Influence of lipopolysaccharides on autophagy and inflammation in pancreatic islet cells of mice fed by high-fat diet. (30th January 2018) - Jiang, Hongwei; Ma, Yujin; Fu, Liujun; Wang, Jie; Wang, Linlei; Fan, Menglin; Huang, Ke; Zhang, Yingyu; Peng, Huifang
The aim of this study was to confirm whether chronic low-grade inflammation could induce autophagy and damage in islet cells. The high-fat diet (HF) and low-dose lipopolysaccharides (LPS) were used to simulate chronic inflammation. Islet function was observed, the expression of autophagy-related proteins and the activity of glucose synthase kinase 3β (GSK-3β) were detected, and the role of autophagy in islet injury induced by inflammation was explored. Higher blood glucose was observed in HF group and LPS group compared with control (C) group, and there was no significant difference between LPS group and LiCl group. The apoptotic pancreatic islet cells in the LPS group were higher than in the HF and C groups, and the in the LiCl group they were higher than in the C group and lower than in the LPS group. Compared with the C group, LC3II/I ratio in the HF group was increased ( P  < 0.05), in LPS and LiCl groups it was lower than in the HF group, and in LiCl group it was higher than in the LPS group. There was no significant difference between HF group and C group with regard to the ratio of p-GSK-3β/GSK-3β, but in the LiCl group it was higher than in the LPS group. The results demonstrated that low-grade inflammation might cause autophagy flux impaired through activation of GSK-3β, and induced islet cells damage. LiCl could play a role in protecting islet cells through autophagy enhancement.